Endothelial nitric oxide synthase localized to hippocampal pyramidal cells: implications for synaptic plasticity. - Dinerman, J L (1994)
Using antibodies that react selectively with peptide sequences unique to endothelial nitric oxide synthase (eNOS), we demonstrate localizations to neuronal populations in the brain. In some brain regions, such as the cerebellum and olfactory bulb, eNOS and neuronal NOS (nNOS) occur in the same cell populations, though in differing proportions. In the hippocampus, localizations of the two enzymes are strikingly different, with eNOS more concentrated in hippocampal pyramidal cells than in any other brain area, whereas nNOS is restricted to occasional interneurons. In many brain regions NADPH diaphorase staining reflects NOS catalytic activity. Hippocampal pyramidal cells do not stain for diaphorase with conventional paraformaldehyde fixation but stain robustly with glutaraldehyde fixatives, presumably reflecting eNOS catalytic activity. eNOS in hippocampal pyramidal cells may generate the NO that has been postulated as a retrograde messenger of long-term potentiation.